Synthesis and characterization of CdS/PVA nanocomposite thin films from a complexing agent free system - Saikia, Dulen; Saikia, P. K.; Gogoi, P. K.; Das, M. R.; Sengupta, P.; Shelke, M. V. (Materials Chemistry and Physics, 2011)
CdS/PVA nanocomposite thin films have been deposited on glass substrates by in situ thermolysis of precursors dispersed in polyvinyl alcohol (PVA). The synthetic technique reported in this study is free from complexing agent and hence no need to control the pH of the solution as in the case of conventional CBD. The as-prepared films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), selected area electron diffraction (SAED), UV-vis spectroscopy, and photoluminescence (PL) spectra. The XRD and SAED results indicated the formation of CdS nanoparticles with hexagonal phase in the PVA matrix. The photoluminescence and UV-vis spectroscopy revealed that CdS/PVA films showed quantum confinement effect. From the shift in optical band gap, particle sizes were calculated using effective mass approximation (EMA) method and it was found to be in agreement with the results obtained from TEM observations. The SEM results indicated that as grown films were homogeneous with no visible pinholes and cracks. The film prepared at 100 degrees C was found to be suitable for application as a window layer in solar cell. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: CdS/PVA; Nanocomposite; Optical properties; Thermolysis

Nutty carbon: morphology replicating hard carbon from walnut shell for na ion battery anode - Wahid, M.; Gawli, Y.; Puthusseri, D.; Kumar, A.; Shelke, M. V.; Ogale, S. (ACS Omega, 2017)
<div id="absImg" style="position: relative; margin: 0px; padding: 5px; border: 1px solid rgb(204, 204, 204); border-radius: 5px; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial; text-align: center; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;"><img alt="Abstract Image" src="http://pubs.acs.org/appl/literatum/publisher/achs/journals/content/acsodf/2017/acsodf.2017.2.issue-7/acsomega.7b00633/20170713/images/medium/ao-2017-00633k_0006.gif" style="border: 0px; max-width: 100%;"> <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">Efficient Na ion intercalation/deintercalation in the semigraphitic lattice of a hard carbon derived from the walnut shell is demonstrated. High-temperature (1000 °C) pyrolysis of walnut shells under an inert atmosphere yields a hard carbon with a low surface area (59 m2 g–1) and a large interplanar c axis separation of 0.39–0.36 nm as compared to 0.32 nm for graphite, suitable for Na ion intercalation/deintercalation. A stable reversible capacity of 257 mAh g–1 is observed at a current density of 50 mA g–1 for such nutshell-derived carbon (NDC) with an impressive rate performance. No loss of electrochemical performance is observed for high current cycling (100 mA g–1 → 2 A g–1 → 100 mA g–1). Additionally, the NDC shows remarkably stable electrochemical performance up to 300 charge–discharge cycles at 100 mA g–1 with a minimal drop in capacity.
Keywords: Batteries; Biological and Medicinal chemistry; Biological materials; diffraction; Electric Properties; Electrode-electrolyte interface; spectra; Surface structure; Thermal properties

Optical antenna effect on SiNWs/CuS photodiodes - Yenchalwar, Sandeep G.; Rondiya, Sachin R.; Shinde, Pravin N.; Jadkar, Sandesh R.; Shelke, M. V. (Physica Status Solidi A-Applications and Materials Science, 2017)
One-dimensional architectures between silicon nanowires (SiNWs) and CuS were fabricated by radio-frequency (RF) magnetron sputtering and analyzed for solid-state photodetector application. Inspired by the subwavelength optical concentration by the surface plasmons on metal nanostructures at the nanoscale, we investigated the effect of gold nanorods (AuNRs) on the optical absorption and photodetection properties of the heterojunction photodiode. AuNRs acting as an optical trapping antenna enhances the light absorption, consequently boosting the photocurrent from the device. A maximum photoresponsivity of 0.36 mA W-1 was achieved under 665 nm excitation wavelength independent of the bias, a value similar to 13 times higher than for the heterojunction photodiode without AuNRs. Such plasmonic sensitization can be useful for improving the sensitivity of visible as well as IR photodetectors. (C) 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim